Dry needling as one of the methods of eliminating myofascial trigger points - Dąbrowska, Maria; Lisiecki, Jakub; Biernacki, Maciej; Grzonkowska, Magdalena; Ulenberg, Agata; Ulenberg, Grzegorz (Journal of Education, Health and Sport, 2018)
Dry needling is one of the methods used to treat myofascial pain syndrome. The treatment involves the use of disposable acupuncture needles but dry needling and acupuncture are not the same. In most cases, the treatment includes myofascial trigger point puncturing. The desired effect to be achieved during the procedure is eliciting a local muscle contraction. The most common response after treatment is pain in the needled area.